Fabrication of high-temperature superconducting nanobridges using atomic force microscopy - Elkaseh, Akram Abdulsalam (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MEng (Electrical and Electronic Engineering))--University of Stellenbosch, 2006.